E-075 Penetrating Intracranial Injury Treated with Fluoroscopically-Guided Noninvasive Removal. (14th July 2013) - Jernigan, S; Gross, B; Green-Hopkins, I; Robinson, S; Orbach, D
Abstract : Background: Spear-like penetrating injuries with retained intracranial foreign bodies have been previously managed with craniotomy and removal in the OR. In this case, with the foreign body traversing both hemispheres, with potential haemorrhage from a large region, we opted for extraction in the angiography suite, with haemorrhage to be managed using endovascular means. Case Report: This 20 month-old fell directly onto a pencil, which penetrated her right superomedial orbital wall. She was grossly neurologically intact, other than right eye movements on arrival to the emergency department. A CTA was performed, showing that 14 cm of the pencil were intracranial, traversing the right orbitofrontal region and much of the left hemisphere. The left MCA was narrowed, but there was no intracranial haemorrhage. The right globe appeared intact. The patient was brought to the angiography suite and the pencil was slowly extracted under flouroscopic-guidance and repeated angiography, first in the left hemisphere, and then in the right, once the tip had crossed the midline. Pre- and post-pull angiography demonstrated near normalisation of the caliber of the left MCA after the pencil was removed. The patient initially had mild right-sided hemiparesis, with near complete resolution on follow-up. Vision and extraocular movements are intact. Discussion: Due to a potentially wide field of sites of haemorrhage in both hemispheres, we opted to extract this foreign object in the angiography suite rather than the OR. The patient remarkably tolerated the initial injury with minimal deficits and there was no morbidity related to the extraction. Disclosures: S. Jernigan: None. B. Gross: None. I. Green-Hopkins: None. S. Robinson: None. D. Orbach: None.